Glycine-assisted enhancement of 1,4-beta-D-xylan xylanohydrolase activity at alkaline pH with a pH optimum shift - Vathipadiekal, Vinod; Verma, Anamika; Rao, Mala (Biological Chemistry, 2007)
This is the first report describing the enhancement of xylanase activity by the neutral amino acid glycine. Xylanase activity is increased seven-fold at alkaline pH in the presence of glycine and its pH optimum is shifted from pH 7 to 8 without using any protein engineering techniques. Analysis of the steady-state kinetics revealed that glycine in the reaction mixture increases the K-m and k(cat) values of the enzyme. Chemoaffinity labeling and studies using glycine esters indicate an involvement of the carboxylate ion of glycine in enhancing xylanase catalytic activity. A novel possible mechanism for the glycine-assisted catalytic action of xylanase is proposed.
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase